2018
DOI: 10.1001/jamaoncol.2017.4777
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oral Microbiome With Risk for Incident Head and Neck Squamous Cell Cancer

Abstract: This study demonstrates that greater oral abundance of commensal Corynebacterium and Kingella is associated with decreased risk of HNSCC, with potential implications for cancer prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
188
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(223 citation statements)
references
References 36 publications
15
188
0
5
Order By: Relevance
“…The results of the current study demonstrated that APG-157 treatment reduces salivary inflammatory cytokines, and this may be directly related to changes in the oral microbiota. Similar to prior reports, 43 the results herein demonstrated that the oral microbiome of patients with cancer is distinct from that of healthy controls (Fig. 3).…”
Section: Discussionsupporting
confidence: 91%
“…The results of the current study demonstrated that APG-157 treatment reduces salivary inflammatory cytokines, and this may be directly related to changes in the oral microbiota. Similar to prior reports, 43 the results herein demonstrated that the oral microbiome of patients with cancer is distinct from that of healthy controls (Fig. 3).…”
Section: Discussionsupporting
confidence: 91%
“…Twenty‐three non‐specific sequence‐based identification studies of the microbiota were included, 14 of which were published in 2017–2018 (Table ) (Al‐Hebshi, Nasher, Idris, & Chen, ; Al‐Hebshi et al., ; Bebek et al., ; Börnigen et al., ; Guerrero‐Preston et al., , ; Hayes et al., ; Hooper et al., ; Hu, Zhang, Hua, & Chen, ; Lee et al., ; Li et al., ; Mukherjee et al., ; Perera et al., , ; Pushalkar et al., , ; Schmidt et al., ; Shin et al., ; Wang et al., ; Wolf et al., ;Yang, Huang et al., ; Yang, Yeh et al., ; Zhao et al., ). Twenty‐one studies focused on bacterial identification (all by 16S rRNA gene regions), one of which also identified fungi (ITS2 gene fragment), one only fungi, and one was restricted to viral identification (human rRNA detection followed by search for viral sequences).…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies examining saliva/oral rinse/mouthwash samples, Hayes et al. () found no significant differences at the genus level between health and disease. In contrast, Guerrero‐Preston et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral microbiome has been suggested as a modulating factor for susceptibility to oral carcinogenesis . Variations in the composition of the oral microbiome are associated with oral cancer . However, the precise role of the microbiome in tumorigenesis is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%